Attitudes of Turkish Veterinary Students and Educators towards the Moral Status of Animals and Species Rating - Ozen, Abdullah; Ozen, Rahsan; Yasar, Askin; Armutak, Altan; Bayrak, Sadik; Gezman, Ahmet; Seker, Ibrahim (Kafkas Univ, Veteriner Fakultesi Dergisi, 2009)
The objective of this study was to determine the attitude of veterinary students and educators about moral status of animals and species rating and to examine the parameters that might have effects on these matters. In this study, veterinary students and veterinary educators from Firat, Istanbul and Selcuk Veterinary Faculties were surveyed. Data were collected from 330 students and 204 educators by a paper questionnaire. Most of the participants showed a positive attitude for moral status of animals (>4). Species rating of the participants were as follows: mammals, birds, fish, reptiles and insects. As a result; it can be said that veterinary educators and students are generally sensitive on moral status of animals but differences in the factors such as academic status, gender, pet keeping and industrialization affected the level of sensitivity significantly (P<0.05). In addition to this, advanced education and increased experience are the factors that may overcome species rating (P<0.05).
Türk veteriner hekimli?i ö?rencilerinin ve e?itimcilerin hayvanların ahlaki konumları ve türlerin derecelendirilmesine i?lişkin tutumları
Keywords: Animal ethics; Moral status of animal; Species ratings; Veterinarian